Coronavirus Disease 2019 Cluster Originating in a Primary School Teachers' Room in Japan. Issue 11 (November 2021) - Aizawa, Yuta; Shobugawa, Yugo; Tomiyama, Nobuko; Nakayama, Hitoshi; Takahashi, Masako; Yanagiya, Junko; Kaji, Noriko; Ikuse, Tatsuki; Izumita, Ryohei; Yamanaka, Takayuki; Hasegawa, Satoshi; Tamura, Tsutomu; et al.
Abstract : Background: School closures are a subject of debate during the present coronavirus disease 2019 (COVID-19) pandemic. Because children are not the main driver of COVID-19 transmission in the community, school education must be prioritized in conjunction with appropriate infection prevention and control measures, as determined by local COVID-19 incidence. Methods: We investigated the causes and transmission routes of a primary school cluster of COVID-19 that occurred during November and December 2020 in Niigata, Japan. Results: In the cluster, the virus spread among teachers, then from teachers to students, and then to their family members. This primary school cluster comprised 26 infected patients and included teachers (13/33, 39%), students (9/211, 4%), and family members (4/65, 6%). The secondary attack rate from the 3 index teachers to the remaining 30 teachers was 33%; however, the rate to students was only 4%. Factors contributing to cluster formation include the fact that 2 of the index teachers continued working while symptomatic and that the environment and infection prevention measures in the teachers' room were inadequate. Conclusions: To open schools safely and without interruption, adequate measures to prevent COVID-19 infection in schools should be emphasized not only for children but also for teachers and their environment. Abstract : Supplemental Digital Content is available in the text.